Some Applications of Fibre Bundle Techniques in Physics - Jessup, Barry (My University, 1979)
Both the theories of differential geometry and of Lie groups and their algebras have been invaluable to the physicist. In the theory of fibre bundles and in the symplectic formulation of mechanics, these fields coalesce to provide a rich structure that enables her/him to obtain a more unified overview of the modern theories in physics. In this short work, we introduce this structure and examine its consequences in general relativity and quantum mechanics.
Keywords: differential, fibre, bundles, structure, relativity, symplectic